2006
DOI: 10.1002/neu.20279
|View full text |Cite
|
Sign up to set email alerts
|

The adult abdominal neuromuscular junction of Drosophila: A model for synaptic plasticity

Abstract: During its life cycle, Drosophila makes two sets of neuromuscular junctions (NMJs), embryonic/larval and adult, which serve distinct stage-specific functions. During metamorphosis, the larval NMJs are restructured to give rise to their adult counterparts, a process that is integrated into the overall remodeling of the nervous system. The NMJs of the prothoracic muscles and the mesothoracic dorsal longitudinal (flight) muscles have been previously described. Given the diversity and complexity of adult muscle gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 47 publications
2
36
0
Order By: Relevance
“…By co-labeling with the neuronal marker 22C10, we found that the ventral muscles in segment A2 are robustly innervated by Hb9-Gal4 expressing neurons, as previously reported (Fig. 5I) (Hebbar et al, 2006). However, in segment A3 Hb9-Gal4 expressing neurons make a much smaller contribution to the ventral muscle innervation (Fig.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…By co-labeling with the neuronal marker 22C10, we found that the ventral muscles in segment A2 are robustly innervated by Hb9-Gal4 expressing neurons, as previously reported (Fig. 5I) (Hebbar et al, 2006). However, in segment A3 Hb9-Gal4 expressing neurons make a much smaller contribution to the ventral muscle innervation (Fig.…”
Section: Resultssupporting
confidence: 88%
“…The Hb9 homeodomain protein is another marker of motor neurons. Some of the ventrally projecting motor neurons express Hb9 (Broihier and Skeath, 2002; Hebbar et al, 2006). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A genetically induced reduction of FasII affects the morphology of adult NMJs by reducing the area, but not the size of individual synaptic boutons. Conversely, a genetically encoded increase of FasII results in increased numbers of boutons and presynaptic area (Hebbar et al 2006).…”
Section: Cams In Nmj Plasticitymentioning
confidence: 99%